LCM-Ufrgs Research Group Report: What are we doing in Computer Music? - Pimenta, Marcelo; Schramm, Rodrigo; Johann, Marcelo (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10442, 2019)
In this paper, we present a historical overview and a brief report of the main recent activities at LCM (Laboratório de Computação Musical) of UFRGS (Universidade Federal do Rio Grande do Sul).